Makna Kebahagiaan dalam Perspektif Anak-anak - Agnes Indar Etikawati (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2021)
Abstract. This article reports the research that conducted to investigate the meaning of happiness in children’s perspectives. The author conducted group interview with 55 students in grades 4 to 6 of elementary school living in Yogyakarta. The children were asked to share their opinion about the image of a happy child. The 64 responses obtained were analyzed thematically and categorized into 8 themes. The two most dominant themes reflect happiness as a state of harmony with others and having a kindness. Happiness is also interpreted as positive feelings, engagement in activities, and positive thoughts. In small number of responses, children associated happiness as a satisfaction related to themselves such as a sense of ability/achievement, live up to expectations, and having freedom. The results indicate that children's happiness contains the same components as adults but with different indicators such as satisfaction in some areas and lower engagement intensity. The results also show that in addition to the universal, there are also typical meaning of happiness due to cultural influences. Therefore, the results of this study suggest paying attention to the characteristics of child development and the local cultural context in seeking happiness for children.Keywords: meaning of happiness, subjective well-being, children’s perspectives